(untitled) (Raparin Journal of Humanities (RJH), 2024)
The random housing phenomenon is one of the Urban Environment’s most significant problem, it is a complex issue that causes multiple problems in the cities, and it is spreading fast, therefore, scientists named it the cancerous expansion. Khabat city had its share of this phenomenon due to its strategic and economic importance. This research aims at addressing this phenomenon using advanced planning and statistical methods. The research presents three main hypothesis, most importantly: statistical methods have the capacity to address the researched problem by showing its levels to achieve the research goal. The research relied on the inductive method. The research plan included four axis in addition to an introduction. The first axis introduces a theoretical frame of the phenomenon. The second axis focuses on the special variation of the studies phenomenon, while the third axis discusses the factors affecting the spread of the phenomenon in Khabat city. The final axis studies ways and methods to address the phenomenon. Finally, the present research has shown a number of conclusions The most important one is random Residences which is in 2021 presently stated as making up of 37% of its entire population, 44% of its housing, and 44.3% of the entire areas in khabat. in all neighborhoods Kabat district has been dividid random Creation of detailed database in the Government agencies and the enforcing the law for punishing those who trespass or violate the rules in residence. excesses are the most important recommendations which has been mention in our research.